Closure of insufficient, native right ventricular outflow tract with AMPLATZER™ muscular ventricular septal defect occluder in a patient with tetralogy of Fallot post-Melody® valve - Neha Bansal; Sanjeev Aggarwal; Daniel R Turner (Wolters Kluwer Medknow Publications, 2019)
AMPLATZER™ muscular ventricular septal defect occluder is used commonly for off-label purposes. We describe an unusual case of a patient with tetralogy of Fallot who underwent repair with a right ventricle to pulmonary artery homograft due to abnormal coronary artery pattern. During the initial surgery, the native right ventricular outflow tract was left open. At 30 years of age, he was symptomatic due to severe native right ventricular outflow tract insufficiency. Cardiac MRI confirmed a dilated right ventricle and pulmonary insufficiency through the native right ventricular outflow tract, despite no significant homograft insufficiency due to previous Melody® valve placement. The right ventricular outflow tract was closed successfully using an 18 mm AMPLATZER™ muscular ventricular septal defect occluder. At 5-year follow-up, there is no native right ventricular outflow tract insufficiency and no additional arrhythmia. We suggest that percutaneous closure of the insufficient; native right ventricular outflow tract using a septal occluder is an alternative to surgical management.